Evaluation of the Success of Programs and Strategy for Sustainable Coastal Community Development in Tanggamus Regency. (February 2020) - Yanfika, H; Rangga, K K; Viantimala, B; Listiana, I; Mutolib, A; Rahmat, A
Abstract: This study aims to analyze the success of the KUB program and the coastal community development strategy in Tanggamus Regency. The research was conducted in Kota Agung Sub-district, Tanggamus Regency, Lampung Province, which is a fishery center in Tanggamus Regency. The study was conducted in July and August 2019. The research method uses a quantitative approach to the survey method. Qualitative data was collected to support research studies through in-depth interviews, focus group discussions (FGD), and field observations. The data collected will be analyzed using qualitative descriptive approaches. The results showed that the capture fisheries program was generally good and following the needs of fishermen to increase catches. Nevertheless, in the implementation of activities in the joint business groups still need to be improved access, because program assistance is still felt by some individuals. Besides, increased communication between group members strengthens joint business groups is needed. The strategy of developing coastal communities in increase independence is through training in processing fishery products, fostering entrepreneurship, policies to limiting fishery products from outside the region, increasing public awareness about of maintaining the cleanliness of the sea and the environment and promote cooperation with stakeholders to support the sustainability of fisheries businesses.